2019
DOI: 10.1016/j.redox.2018.101085
|View full text |Cite
|
Sign up to set email alerts
|

Specific delivery of delta-5-desaturase siRNA via RNA nanoparticles supplemented with dihomo-γ-linolenic acid for colon cancer suppression

Abstract: We have previously demonstrated that DGLA treatment along with Delta-5-Desaturase (D5D) siRNA in various types of cancer cells enhances the formation of 8-HOA from COX-2-catalyzed DGLA peroxidation, which in turn inhibits cancer cell growth and migration. However, delivery of naked siRNA remains a formidable challenge due to its “off-target” effect. In this study, we employed RNA nanotechnology for specific delivery of D5D-siRNA to xenograft colon tumors using 3WJ RNA nanoparticles. When a targeting module, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 40 publications
1
47
0
Order By: Relevance
“…44,45 Thus, the anti-inflammatory property of DGLA and its ability to compete with AA in the synthesis of pro-inflammatory products may reduce risk of colorectal cancer. 45,46 As for EDA, a previous study found that EDA was inversely associated with colorectal cancer. The anti-inflammatory effect of EDA has been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…44,45 Thus, the anti-inflammatory property of DGLA and its ability to compete with AA in the synthesis of pro-inflammatory products may reduce risk of colorectal cancer. 45,46 As for EDA, a previous study found that EDA was inversely associated with colorectal cancer. The anti-inflammatory effect of EDA has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…DGLA is a substrate of prostaglandin‐endoperoxide synthase 2, giving rise to prostaglandin E1 (PGE 1 ), an inflammation‐suppressing eicosanoids 44,45 . Thus, the anti‐inflammatory property of DGLA and its ability to compete with AA in the synthesis of pro‐inflammatory products may reduce risk of colorectal cancer 45,46 . As for EDA, a previous study found that EDA was inversely associated with colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…6); (iii) extracellular vesicles or exosomes derived from various cell types (Fig. 5f, m); 16,238,239 (iv) peptides; [240][241][242][243] (v) dendrimers; [244][245][246] (vi) RNA nanoparticles (e.g., three way-junction, 3WJ); [247][248][249][250][251][252][253][254] and (vii) inorganic nanoparticles 229,255 (Fig. 6).…”
Section: Galnac-sirna Conjugatesmentioning
confidence: 99%
“…This non‐specificity not only distracts nanoparticles from transporting to tumors, but also causes toxicity and unwanted side effects. To address this challenge, Guo Lab has developed a series of pRNA‐3WJ based RNA nanoparticles incorporated with targeting ligands (Binzel et al, ; Cui et al, ; Lee et al, ; Pi et al, ; Rychahou et al, ; Shu et al, ; Shu et al, ; Shu, Haque, et al, ; Xu et al, ). Upon systemic administration in tumor‐bearing mice, these RNA nanoparticles specifically transport to tumors within about 4 hours (h), and successfully remain at the tumor site for over 24 h. No or minimal organ accumulation was detected several hours post‐injection.…”
Section: Advantages Of Rna Nanotechnology For Cancer Targeting and Immentioning
confidence: 99%